Drug-induced systemic lupus erythematosus in interferon beta-1b therapy - Sladkova, Vladimira; Mares, Jan; Lubenova, Blanka; Hlustik, Petr; Kanovsky, Petr (Neuro endocrinology letters, 2011)
Drug-induced systemic lupus erythematosus (SLE) is a rare complication of therapies with some drugs. Breaking out after months or years of therapy with a certain drug, its occurrence is likely to increase with the duration of the medication and the cumulative quantity of the drug. The symptoms of this syndrome include, in particular, arthralgia, myalgia, fever, serositis, skin exanthema and production of antinuclear (ANA) antibodies. In contrast to SLE, its symptoms gradually abate after discontinuation of the inducing agent. The authors describe the case of a 43-year-old patient suffering from multiple sclerosis who experienced drug-induced SLE after 8-year application of interferon (IFN) beta-1b.
Keywords: interferon beta; dospělí; Adult; adjuvancia imunologická; lidé; systémový lupus erythematodes; Interferon-beta; interferon beta 1b; Adjuvants, Immunologic; Multiple Sclerosis, Relapsing-Remitting; Time Factors; relabující-remitující roztroušená skleróza; Humans; časové faktory; Interferon beta-1b; Lupus Erythematosus, Systemic; ženské pohlaví; Female